Vietnamese EFL Majors’ Emotional Experiences in Thesis Writing: A PERMA-Informed Qualitative Multiple-Case Study - Phan Nhat Hao (Scientia Publica Media, 2026)
Emotions constitute a central dimension of students’ academic development in higher and continuing education. While the body of literature has examined affective experiences in learning contexts, emotional trajectories embedded in extended academic tasks remain insufficiently theorized. In language education programs, the graduation thesis is deemed an academically demanding task that intertwines cognitive challenges, relational dynamics, and identity development, warranting a further systematic investigation. Addressing this gap, the current study examined how Vietnamese English-as-a-Foreign-Language (EFL) majors experienced emotions during the thesis-writing process in the Mekong Delta region. Using a PERMA-informed qualitative multiple-case design, the study involved six students at a public university. Data were qualitatively generated by their in-depth semi-structured interviews, reflective journals, and documentary artifacts. Analysis followed a hybrid data-coding approach integrating theory-informed and inductive procedures, with within- and cross-case comparisons strengthening interpretive depth. Findings revealed multidimensional emotional experiences organized around five elements. “Positive Emotion” encompassed anticipatory hope, progress-related joy, and earned pride at thesis completion. “Engagement” was reflected in sustained cognitive immersion and disciplined self-regulation. “Relationships” with thesis supervisors and peers contributed to relational validation and academic belonging. “Meaning” developed through intellectual growth and identity repositioning toward emerging researcherhood. “Accomplishment” consolidated competence, strengthened self-efficacy, and generated forward-oriented aspirations. The study contributed a contextually grounded account of emotional experiences in thesis writing, through which it advanced current understandings of English language education in Vietnam and beyond. Implications highlighted the importance of supportive supervision and research training that cultivate well-being alongside academic rigor. The study concluded with limitations and offered methodological recommendations for future investigations.